Shadow Banking - A Geographical Interpretation - Gianfranco Battisti (European Regional Science Association (ERSA), 2014)
Basically, shadow banking is an original kind of business organization, or better a set of institutions and markets, finalized to disinvest fixed assets and convey them to the financial markets. Nowadays, tackling the subject means penetrating the hard core of financialization. Shadow banking manifests itself through a variety of activities carried out since time immemorial. Some authors go back to the 17th century, but certain procedures and entire phases were established well before the institutionalization of banks as we know them. Suffice it to think of the so-called trinus contractus, developed to bypass the canonical prohibition of commercial loans during the Middle Ages. Although its structure was active in the 30s, at a time of global financial troubles, it attracted the attention of a wider public only with the outburst of the present crisis (McCulley, 2007). The first analyses made in the frame of national institutions (Geithner, 2008) and international bodies (Tett and Davies, 2007) were carried out due to the emergency, thus projecting on it a negative light. The tendency is to consider shadow banking as an anomaly of financial markets, to which it appears thoroughly linked. In this paper we try to analyze the subject from a structural point of view, within the wider context of globalized economy. A comparison with the 'official' banking system is proposed, trying to draw a parallel with the evolution experienced by other economic sectors. To begin with, it is noteworthy that the functions performed are basically of the same nature, i.e. credit brockerage. Three main differences are to be considered: 1) the system is not recognized and therefore neither assessed, nor regulated; 2) the lack of regulations produced a lack of homogeneity: we are not simply facing a parallel market, but a completely different structure; 3) this does not develop 'under one roof', but is fragmented in a variety of companies. All this stresses the scarce visibility of the sector, hence the nickname of 'shadow'. As for the 'official' banking, the relationship is both competitive and cooperative, so the anomaly is to be credited to the entire credit/finance sector, that has been duplicating at a certain degree. The influence of this process on the spatial distribution of the systemic elements will also be discussed.
Keywords: G1; G2; N2; 330; financialization; financial geography; globalization; shadow banking